2015
DOI: 10.4067/s0717-95022015000400057
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry, Handedness and Auricle Morphometry

Abstract: SUMMARY:The aims of this study were to determine various morphometric measurements of auricle, to investigate asymmetry and its relation with handedness in both sexes. Main morphometric measurements of both auricles and hand preferences were determined on 200 male and 200 female healthy university students. All measurements of the auricles were larger in males than the corresponding ones in females and all the differences except earlobe widths were statistically significant. All measurements of left and right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Alexander et al (2011) discovered that linear dimensions, including height and width, showed a higher symmetry, while angular measurements had less symmetry between the left and right sides. Tatlisumak et al (2015) reported left ear length was significantly longer than the right length for the Turkish population while Jung and Jung (2003) concluded that Koreans have longer ear length on the right than the left side. These studies provided statistical findings of selected ear dimensions upon variables of population, age, gender, and symmetry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alexander et al (2011) discovered that linear dimensions, including height and width, showed a higher symmetry, while angular measurements had less symmetry between the left and right sides. Tatlisumak et al (2015) reported left ear length was significantly longer than the right length for the Turkish population while Jung and Jung (2003) concluded that Koreans have longer ear length on the right than the left side. These studies provided statistical findings of selected ear dimensions upon variables of population, age, gender, and symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of (a) traditional measurement, (b) photogrammetric measurement (Ma et al, 2017), and (c) 3D scanning measurement Hossein, Payam, and Masih (2018) determined that Hamadan men had significantly greater ear size than Caucasian men. In regard to gender differences, these investigations revealed that females have smaller ear length and width than males for Korean (Jung & Jung, 2003), Turkish (Barut & Aktunc, 2006;Tatlisumak et al, 2015), and Italian peoples (Sforza et al, 2009). Alexander et al (2011) discovered that linear dimensions, including height and width, showed a higher symmetry, while angular measurements had less symmetry between the left and right sides.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most intricate body parts to model aside from the head is the auricle of the ear. Detailed information of the morphology, dimensions, location, and asymmetry of normal auricles is essential for diagnosing congenital abnormalities and syndromes, conducting forensic investigations, and ergonomically designing ear-related products (Coward et al, 2000;Purkait & Singh, 2007;Tatlisumak et al, 2015). Regardless of ethnicity, the literature shows that the mean dimensions of the auricle are larger in males than females, as evidenced by the numerous anthropometric studies that focus on the auricles of different ethnic groups, such as the Chinese (Liu, 2008;Wang et al, 2011;Yu et al, 2015;Zhu et al, 2017;Zhao et al, 2018;Fan et al, 2019), Koreans (Jung & Jung, 2003;Kang et al, 2006;Han et al, 2010;Lee et al, 2018), Malaysians (Kumar & Selvi, 2016), Indians (Purkait & Singh;Sharma et al, 2007;Purkait, 2013;Singhal et al, 2016), Sudanese Arabs (Ahmed & Omer, 2015), Italians (Russo, 1998;Ferrario et al,1999;Sforza et al, 2009), and Britons (Coward et al;Alexander et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is wellestablished fact that a detailed knowledge of the morphologic dimensions, location and asymmetry of normal auricle is essential for the diagnosis of congenital abnormalities and syndromes, forensic investigations and for the ergonomic design of hearing aids (Coward et al, 2000;Purkait & Singh, 2007;Tatlisumak et al, 2015). Therefore, a large number of anthropometric studies of normal auricle have been assessed in various populations, for instance, Koreans (Jung & Jung, 2003;Kang et al, 2006), Sudanese Arabs (Ahmed & Omer), Chinese (Liu, 2008;Wang et al, 2011) Indians (Purkait & Singh;Sharma et al, 2007;Purkait, 2013), Italians (GualdiRusso, 1998;Ferrario et al, 1999;Sforza et al, 2009), Britons (Coward et al; Alexander et al), Turks (Bozkir et al, 2006;Barut & Aktunc, 2006), Americans (Brucker et al, 2003), Germans (Niemitz et al, 2007), and Japanese (Asai et al, 1996).…”
Section: Introductionmentioning
confidence: 99%